Intranasal dexmedetomidine sedation for paediatric MRI by radiology personnel: A retrospective observational study. Issue 3 (22nd March 2023) - Karlsson, Jacob; Lewis, Gabriella; Larsson, Peter; Lönnqvist, Per-Arne; Diaz, Sandra
Abstract : BACKGROUND: MRI often requires sedation or anaesthesia to ensure good image quality in paediatric patients. Access to paediatric anaesthesia services is, however, a limiting factor for effective paediatric MRI service, and alternative sedation methods are, therefore, warranted. OBJECTIVE: To investigate the efficacy and safety of an intranasal dexmedetomidine sedation program for paediatric MRI, without immediate presence of anaesthesia personnel. DESIGN: Single institution retrospective observational study. SETTING: Tertiary care paediatric hospital. PATIENTS: Children 0 to 12 years, ASA risk class 1 or 2 with heart rate within age-appropriate limit. INTERVENTION: Radiology personnel administered an initial dose of intranasal dexmedetomidine of 4 μg kg −1 followed by a second dose of 2 μg kg −1 to the patients if needed. Recordings of image quality, critical events, heart rate, pulse oximetry saturation and noninvasive blood pressure before and after dexmedetomidine administration were made. MAIN OUTCOME MEASURES: Changes in haemodynamic and respiratory data before vs. after intranasal dexmedetomidine were analysed for changes, and the incidence of critical events was evaluated as well as rate of successful MRI scans. RESULTS: One thousand and ninety-one MRIs under intranasal dexmedetomidine sedation were included (mean age 34 months, 95% confidence interval (CI), 33 to 36, 599 male individuals). A success rate of 93% (95% CI, 91 to 94%) was found. No major critical events were recorded, total incidence of minor issues was 0.2% (95% CI, 0 to 0.7%). Five children had a heart rate under a preset minimal limit after dexmedetomidine (0.4%; 95% CI, 0.1 to 0.9%). Significant decreases in heart rate and mean arterial pressure, within acceptable limits not requiring intervention, was seen after dexmedetomidine administration. CONCLUSION: Intranasal dexmedetomidine sedation without immediate presence of anaesthesia personnel appears to be well tolerated and associated with minimal interference on MRI image quality. TRIAL REGISTRATION: clinicaltrials.org NCT05163704, retrospectively registered.